The status quo of distance education at the Faculty of Education - Tripoli in light of the Corona pandemic (Journal of Human Sciences, 2021)
The study aimed to identify the educational patterns used by the teaching staff at the Faculty of Education - Tripoli in light of the Corona pandemic in performing lectures, following up on assignments, and implementing midterm exams (in-person - distance - combining in-person and distance education), and the relationship of the use of distance education with some variables (specialization, qualification, gender, experience), as well as identifying the difficulties facing faculty members at the Faculty of Education  Tripoli in applying distance education and its relationship to the above mentioned variables .The researcher used the descriptive analytical method, and the questionnaire as a research tool.The study sample consisted of (66) faculty members, which constituted (38.82%) of the study population.The study reached the following results:• (46.97%) of the sample members used only in-person teaching in providing lectures, (28.79%) used distance education, while (24.24%) of them combined both in-person and distance education.• (42.42%) of the sample members used only in-person follow up on homework assignments, (15.15%) used distance education, while (42.42%) of them combined both in-person and distance education.• All members of the sample gave midterm exams in-person (100%).• The most widely used tools in distance education are Telegram (27.77%), printed lectures (15.55%،( and then Whats App (11.11%).• There are no statistically significant differences in the sample members' use of distance education attributed to the variables (specialization, degree, gender), and there were statistically significant differences attributed to experience in favor of the most experienced.• The average difficulties facing distance education are moderate.7. There are no statistically significant differences between the average responses of the sample members towards the difficulties facing distance education attributed to the variables (specialization, qualification, gender, experience).